2021
DOI: 10.1021/jacs.1c08671
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Enabled Electrochemical Enantioselective Oxidative Coupling of Secondary Acyclic Amines with Ketones

Abstract: An electrochemical asymmetric coupling of secondary acyclic amines with ketones via a Shono-type oxidation has been described, affording the corresponding amino acid derivatives with good to excellent diastereoselectivity and enantioselectivity. The addition of an N-oxyl radical as a redox mediator could selectively oxidize the substrate rather than the product, although their oxidation potential difference is subtle (about 13 mV). This electrochemical transformation proceeds in the absence of stoichiometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 74 publications
0
56
0
1
Order By: Relevance
“…Based on the above experiments and literature, [33–38, 43–47] a possible mechanism was proposed (Figure 3). The reaction initiates with ACT oxidation at the anode to give ACT + .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the above experiments and literature, [33–38, 43–47] a possible mechanism was proposed (Figure 3). The reaction initiates with ACT oxidation at the anode to give ACT + .…”
Section: Resultsmentioning
confidence: 98%
“…Meanwhile, by‐product 4 formed from the oxidative self‐coupling of 1 a was isolated in 54 % yield. Since redox mediators can facilitate the oxidation process under milder reaction conditions at lower electrode potentials, [38] mediator screening was performed (Supporting Information, Tables S1 and S2). The results showed that the addition of 4‐acetamido‐2,2,6,6‐tetramethyl‐1‐piperidineoxy (ACT) could significantly inhibit the generation of 4 and improved the yield of 3 a to 52 %.…”
Section: Resultsmentioning
confidence: 99%
“…The last example of this review comes from the research group of Mei (Scheme 25). 39 They reported an electrochemical oxidative asymmetric Mannich reaction of glycine esters with cyclic ketones, which was unprecedented. TEMPO was employed as a redox mediator in this study, effectively avoiding the excessive oxidation of the products.…”
Section: Asymmetric Electrochemical Oxidative Mannich Reactionsmentioning
confidence: 99%
“…116 In 2021, Mei reported an electrochemical enantioselective Shono-type oxidative coupling of N-arylglycines with ketones using TEMPO as a mediator and β-proline as an organocatalyst. 117 Some cyclic amines can also be employed as the substrate (Scheme 16). Liu et al reported the diastereoselective oxidative alkynylation/allylation of 2-substituted tetrahydropyridines to give 2,6-disubstituted tetrahydropyridines.…”
Section: R 1 Armentioning
confidence: 99%